Retinol saturase promotes tubulointerstitial fibrosis in diabetic kidney disease by inhibiting ChREBP ubiquitination via Smurf2 suppression - Huang, Heming; Xu, Wei; Wang, Yang; Shi, Yanjia; Tang, Sijing; Fang, Ping; Pan, Lingling; Ye, Zhengqin; Zhou, Yun; Huang, Jieli; Xue, Ying (Frontiers in Endocrinology, 2026)
BackgroundRenal tubulointerstitial fibrosis (TIF) is a hallmark pathological feature of diabetic kidney disease (DKD). This study investigates the role and molecular mechanisms of retinol saturase (RetSat) in DKD-associated TIF.MethodsRetSat expression was assessed in renal tissues from DKD patients and mice and correlated with the severity of TIF. Functional experiments were conducted in vitro using HK2 cells to evaluate the effects of RetSat overexpression and knockdown on high-glucose-induced tubular injury and fibrosis. Mechanistically, we examined the expression of the E3 ubiquitin ligase SMAD ubiquitination regulatory factor 2 (Smurf2), carbohydrate-responsive element-binding protein (ChREBP), and various fibrosis markers. Furthermore, the protein-protein interaction and ubiquitination relationship between RetSat and Smurf2 were explored.ResultsRetSat expression was significantly up regulated in the renal tissues of both DKD patients and mice, correlating with the deterioration of TIF. In vitro, RetSat overexpression exacerbated high-glucose-induced tubular injury and fibrosis in HK2 cells, whereas RetSat knockdown attenuated these pathological phenotypes. Mechanistically, RetSat interacted with Smurf2 and promoted its degradation via ubiquitination. This reduction in Smurf2 subsequently prevented the Smurf2-mediated ubiquitination of ChREBP, leading to ChREBP accumulation and the up regulation of tubular injury and fibrosis markers.ConclusionThese findings indicate that RetSat promotes TIF in DKD by disrupting the Smurf2-ChREBP ubiquitination axis, highlighting RetSat as a promising therapeutic target for DKD.